Microwave hydrodiffusion and gravity (MHG) processing of Laminaria ochroleuca brown seaweed. (1st October 2018) - López-Hortas, L.; Gannon, L.; Moreira, R.; Chenlo, F.; Domínguez, H.; Torres, M.D.
Abstract: Microwave hydrodiffusion and gravity (MHG) technique was proposed for the dehydration of edible Laminaria ochroleuca brown seaweed and the recovery of the bioactive compounds. The effect of irradiation power (50, 300 and 800 W) and time (below 180 min) on the drying kinetics and its modelling, shrinkage, energy consumption, microstructural and colorimetric features were studied for the solid phase. In parallel, the phenolic content and scavenging capacity were determined for the solid phase. Results showed that the increase in irradiation power from 50 to 800 W led to the drop of the drying times from 180 to 5 min, although with high final moisture contents (20.78 ± 1.20 and 58.24 ± 3.75% wet basis, w.b., respectively). MHG proposed treatment to obtain the optimum L. ochroleuca drying conditions (9.90 ± 0.81% w.b.) was a four steps protocol: 300 W for 5 min followed by 100 W for 10 min, 50 W for 35 min and 25 W for 90 min. All drying kinetics were successfully (R 2  > 0.95) fitted with the Page model. An adequate lineal dependence (R 2  > 0.94) between shrinkage and moisture content was found. The energy consumption for MHG proposed method was about two decades lower than the values reported for conventional convective air drying of other brown seaweeds. The method settled down provided microstructural, colorimetric and antioxidant capacity properties comparable to the commercially dehydrated seaweed. Graphical abstract: Highlights: Microwave hydrodiffusion and gravity (MHG) was used for L. ochroleuca dehydratation. Sequential irradiation powers and time led to required final water moisture content. MHG proposed method involved a drop (≈100 times) on the required energy consumption. MHG kept the microstructural, colorimetric and antioxidant capacity features. L. ochroleuca MHG-treated showed similar values to commercial dehydrated seaweed.